Development of Young’s Modulus of Illite/Smectite—CaCO3 Composites After Various Firing Temperatures - Štefan Csáki; Tibor Kovács; Martin Keppert; Vojtěch Pommer; František Lukáč; Michal Knapek; Peter Minárik; Anton Trník (Crystals)
Illitic clays are one of the most important materials used in the ceramic industry. Carbonates support the densification and the sintering of ceramics. Five mixtures of illitic clay with calcite were prepared aiming for the crystallization of anorthite ceramics. The stoichiometric ratio of anorthite crystallization was determined at 21.6 wt.% of calcite content. To reveal the effect of calcite on the crystallization processes, two more mixtures were prepared below the stoichiometric composition (17.6 wt.% and 19.6 wt.%) and two more mixtures above the ideal composition (23.6 wt.% and 25.6 wt.%). X-ray diffraction revealed that gehlenite and Ca-feldspar were formed, which are the intermediate phases in anorthite crystallization. However, due to the low purity of illitic clay and the low firing temperature, no anorthite formation was observed. The influence of calcite content on Young’s modulus was negligible. However, a clear effect on the open porosity was revealed.